Students’ Perception on the Advantages of Using Quillbot in Their English Learning - Andika Guruh Saputra; Suswati Hendriani (Universitas Islam Negeri Palopo, 2024)
Artificial intelligence is something that is also part of the modern era and helping many people in English Learning, this study aimed to find out students' perception on the advantages of using QuillBot in their English learning, by looking at the benefits of the use of all classes of students in the English Teaching Department, how they perceive this application, to determine how many students use QuillBot, this is assisted by an Open-ended Question which is distributed in advance to classes 21-24 using Google form after the data is obtained then the data is classified into each class then interviewed, then the data is processed by transcribing and reducing the data until it gets saturated data from the perceptions of students in each class. The results found that there were 16 student perceptions about the use of QuillBot in English Learning that helped them in their Writing, reading, and Speaking skills, so it can be concluded that the use of QuillBot in English Learning provides many benefits.